Factors affecting the environment of the city of Vladivostok - Giyasov Botir; Giyasov Ruslan (E3S Web of Conferences, 2021)
The problem of environment degradation in cities due to the development of megalopolises is demanding urgent attention. The rapid growth of modern cities caused by the need to improve the living conditions contributes to the construction of new buildings and structures, the development of transport and engineering networks. As a result, the density of urban environment increases, the congestion of transport networks increases, leading to environmental pollution and aggravating the environmental situation in cities. The article is devoted to the analysis of the environment of major cities in Russia using the example of the city of Vladivostok. The main factors influencing the environmental pollution, which are characteristic only of modern cities, have been identified. The relationship between energy consumption by various branches of the economy and environmental pollution has been established. Using the example of the city of Vladivostok, the analysis of the aerodynamics of the urban space is carried out, and the parameters for changing the wind speed with the changes in the height of the building have been revealed. The role of convective flows in improving the urban environment has been justified. The main reasons aggravating the environment of cities have been found out. These include significant harmful emissions from vehicles and air exchange in urban areas disturbed due to dense buildings, which leads to a high concentration of harmful substances that pollute the city.